Physicochemical and Microbial Quality of Drinking Water at Gorkha, Nepal - Malla-Pradhan, Rajeshwori; Pradhan, Bijay Lal; Lalkarn, Lalbabu; Shrestha, Rabikiran (Morgan Journal of Interdisciplinary Research Studies, 2024)
To assess the drinking water quality of Bhimsen Thapa Rural Municipality-6, situated in Gorkha district of Nepal, the physicochemical parameters like pH, electrical conductivity, total hardness, ammonia, and nitrate content were investigated using standard procedures. Likewise, for microbiological parameter coliform presence and absence was analyzed. A total of 37 samples were collected from four sampling stations ( the water source, water reservoir, point of collection, and household water storage) in the last week of November 2022 using simple random sampling for tap water and stratified random sampling for household water storage. When comparing the results with the National Drinking Water Quality Standards (NDWQS), 2005 and World Health Organization (WHO), 2004 guidelines, it was observed that most of the physiochemical parameters were within the standards. Based on the microbiological parameter, in most of the water samples during the study coliforms were detected indicating potential health hazards. Therefore, the findings suggest that water from these sources can be considered safe for drinking only after undergoing purification treatment. Urgent attention from relevant authorities is imperative to implement treatment measures for drinking water to ensure its safety before consumption.